Assessing the Impact of Nirsevimab Immunization on RSV Bronchiolitis Hospital Admissions and Their Severity: A Case‐Control Study and Comparison With Pre‐ and Post‐COVID‐19 Seasons in a Tertiary Pediatric Hospital - Guerrero‐del‐Cueto, Fuensanta; Lobato‐López, Sara; Lozano‐Durán, Diego; Sánchez‐Durán, Blanca; Ramírez‐Martín, Lucía; Esteban‐San‐Narciso, Begoña; Sosa‐Hernández, Sara; Martín‐Pedraz, Laura; Moreno‐Pérez, David; Leiva‐Gea, Isabel; Núñez‐Cuadros, Esmeralda (Wiley, 2025)
Introduction: This study evaluates nirsevimab's real‐world effectiveness in preventing respiratory syncytial virus (RSV) bronchiolitis hospitalizations after its introduction in Andalusia's immunization schedule, compares clinical outcomes between immunized and non‐immunized infants (2023–2024), and examines RSV seasonality pre‐ and post‐COVID‐19. Methods: Retrospective single‐center case‐control study conducted at a tertiary pediatric hospital (Malaga Regional University Hospital). Infants hospitalized for PCR‐confirmed RSV bronchiolitis during the first season after nirsevimab introduction were matched with two controls born on the same day. Immunization status, demographic data, and clinical outcomes were analyzed. As a secondary analysis, clinical characteristics and adverse outcomes of immunized and non‐immunized RSV bronchiolitis cases from the 2023–2024 season were compared with four previous periods: pre‐pandemic decade (04/2010–03/ 2020), first pandemic season (04/2020–03/2021), second pandemic season (04/2021–03/2022) and third pandemic season (04/ 2022–03/2023). Results: Nirsevimab showed 91.5% effectiveness (95% CI: 71.8%–97.4%) in reducing RSV bronchiolitis hospitalizations, which decreased 72.4% from the pre‐pandemic average and 82.4% from 04/2022–03/2023. Intensive‐care‐unit admissions were sig- nificantly higher in non‐immunized infants (60.0% vs. 26.1%, p = 0.04), with no differences in bacterial superinfection, oxygen requirement and length‐of‐stay. Conclusions: Nirsevimab significantly reduced RSV bronchiolitis hospitalizations during its first season of use. The study also highlights shifts in RSV seasonality trends influenced by the COVID‐19 pandemic, highlighting the need for ongoing sur- veillance to adapt public health strategies.
Keywords: Bronquios - Enfermedades; Epidemiología pediátrica - Andalucía; COVID-19; Bronchiolitis; Epidemiology; Immunization; Nirsevimab; Respiratory syncytial virus (RSV)